Process Improvement of Adeno-Associated Virus Production - Guan, Jia-Shiung; Chen, Kai; Si, Yingnan; Kim, Taehyun; Zhou, Zhuoxin; Kim, Seulhee; Zhou, Lufang; Liu, Xiaoguang (Frontiers in Chemical Engineering, 2022)
Adeno-associated viruses (AAVs) have been well characterized and used to deliver therapeutic genes for diseases treatment in clinics and basic research. This study used the triple transient transfection of AAV-DJ/8 as a model expression system to develop and optimize the laboratory production of AAV for research and pre-clinical applications. Specifically, various production parameters, including host cell, transfection reagent, cell density, ratio of plasmid DNA and cells, gene size, and production mode, were tested to determine the optimal process. Our results showed that the adherent production using HEK 293AAV with calcium transfection generated the highest volumetric productivity of 7.86 × 109 gc/ml. The optimal suspensive production using HEK 293F had best AAV productivity of 5.78 × 109 gc/ml in serum-free medium under transfection conditions of transfection density of 0.4 × 106 cells/ml, plasmid DNA:cells ratio of 1.6 µg:106 cells and synthesized cationic liposomes as transfection reagent. The similar AAV productivity was confirmed at scales of 30–450 ml in shaker and/or spinner flasks. The in vitro transfection and in vivo infection efficiency of the harvested AAV-DJ/8 carrying luciferase reporter gene was confirmed using cell line and xenograft mouse model, respectively. The minimal or low purification recovery rate of AAV-DJ/8 in ion-exchange chromatography column and affinity column was observed in this study. In summary, we developed and optimized a scalable suspensive production of AAV to support the large-scale preclinical animal studies in research laboratories.